Some Archival Examples of Neglected Cultural Capital - Tomić, Svetlana (Poznańskie Studia Slawistyczne, 2016)
Archives are important places for researching and reconstructing the past, they lead to discoveries, and they can refute dominant stereotypes. Despite that fact, Serbian feminist scholars have neglected archival research of women writers. In this paper the author points out to resistance of the main Serbian institutions to digitalize archival sources of women writers and indicates some consequences of contemporary feminists’ stance to historical sources. The author directs attention to some important but ignored examples of archival materials in Serbia and Bosnia and Herzegovina. Since they offer informative, significant, and complex account on the past, they can help reconstruct of the South Slavic culture and establish the importance of women writers. Keywords